Correction: Great prospects for PAF-1 and its derivatives. Issue 4 (22nd July 2015) - Pei, Cuiying; Ben, Teng; Qiu, Shilun
<x xml:space="preserve">Abstract</x> Correction for 'Great prospects for PAF-1 and its derivatives' by Cuiying Pei et al., Mater. Horiz., 2015, 2, 11–21.